GURU DAN KARYAWAN KATOLIK SEBAGAI SAKSI INJIL DI SEKOLAH - Agustinus Supriyadi (Bahasa Indonesia, 2019)
The times changing. Thus also change the dynamics of human life. And in these changes, contains elements call for disciples of Christ to carry out the testimony of the Gospel and the truth. Catholic teachers and employees are called to bear witness to the Gospel through their concrete life. The call to duty and they need to learn from Jesus himself as an exemplary witness. And this, faith in Jesus becomes the basis of which strengthen them to be witnesses ofthe Gospel. Being a witness to the Gospel, first of all directed towards integral human safety. To support these efforts, need to be presented through live testimony is relevant in the context of the student. Teachers and employees of Catholic at schools, are called to take action testimony. This action not only covers the areas of teaching and the work of a rigid, or limited formal responsibilities, but also the field of witness of life (good deeds). With her they also serve the students and their context. The focus is not on science, but students with all ofits dimensions.